The Wearable Co-Design Domino: A User-Centered Methodology to Co-Design and Co-Evaluate Wearables - Leire Francés Morcillo; Paz Morer-Camo; María Isabel Rodriguez Ferradas; Aitor Cazón Martín (Sensors, 2020)
This paper presents a user-centered methodology to co-design and co-evaluate wearables that has been developed following a research-through design methodology. It has been based on the principles of human–computer interaction and on an empirical case entitled “Design and Development of a Low-Cost Wearable Glove to Track Forces Exerted by Workers in Car Assembly Lines” published in Sensors. Insights from both studies have been used to develop the wearable co-design domino presented in this study. The methodology consists of different design stages composed of an ideation stage, digital service development and test stages, hardware development and test stage, and a final test stage. The main conclusions state that it is necessary to maintain a close relationship between human factors and technical factors when designing wearable. Additionally, through the several studies, it has been concluded that there is need of different field experts that should co-design and co-evaluate wearable iteratively and involving users from the beginning of the process.